Jatun Yacu Eco Lode - Chacón Tipán, Karla Yéssica (2012)
In the first instance with the identification of the opportunities of business, Jatun Yacu Echo Lodge, is a tourist and hotel project, which heinhales to design and to implement one of the best tourist Amazonian products, in province of Napo, with a concept based on practices of sustainable tourism, where a balance and responsibility exists as for the sociocultural, environmental and economic topics. In order to cover increasing needs on a market of green conscience, in tourists who seek to realize his tourist activity of way compromised with the nature...